2008
DOI: 10.1117/1.2870114
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effects of 30% hydrogen peroxide on human tooth enamel by Raman scattering and laser-induced fluorescence

Abstract: The safety of tooth bleaching, which is based upon hydrogen peroxide (HP) as the active agent, has been questioned. Our aim was to investigate the effects of 30% HP on human tooth enamel. The specimens were divided randomly into three groups and treated with distilled water, HCl, and HP, respectively. Raman scattering and laser-induced fluorescence of enamel were determined before and after treatment. Microhardness testing and scanning electron microscopy were also used. The results of Raman scattering showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
117
0
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 105 publications
(131 citation statements)
references
References 29 publications
7
117
0
7
Order By: Relevance
“…Similar to FTIR, Raman spectroscopy has the ability to analyze chemical composition at a molecular level. It is known that laserinduced fluorescence can provide useful information about organic matter [12,25]. Consequently, the higher FI value in the hypomaturation enamel also indicated a higher organic content.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Similar to FTIR, Raman spectroscopy has the ability to analyze chemical composition at a molecular level. It is known that laserinduced fluorescence can provide useful information about organic matter [12,25]. Consequently, the higher FI value in the hypomaturation enamel also indicated a higher organic content.…”
Section: Discussionmentioning
confidence: 97%
“…It was found that hypomaturation enamel showed a lower mean RRI value than normal enamel. Since the RRI from the Raman spectra is linearly proportional to the phosphate group concentration within HAP molecules [43,44] and phosphate group concentration is a good indicator of the degree of mineralization in enamel [12,24,25,44], a lower mean RRI value is expected for the lower mineral content of hypomaturation enamel.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Some studies reported that there was no evident change in enamel microhardness and morphology after bleaching treatment. [4][5][6][7] But others have found calcium loss, [8][9][10] alterations of surface morphology, [11][12][13][14][15] changes in chemical composition, 10,[15][16][17][18] decrease in hardness 10,15,[19][20][21][22] and fracture resistance 23 of enamel. The divergence in these results is probably related to different methodologies (in vivo or in vitro, time of evaluation, bleaching agents used, time of application, immersion of the specimens in artificial saliva between treatments, type of storage, bleaching agent pH, usage of fluoride, etc.).…”
Section: Introductionmentioning
confidence: 99%